‘Guided Economics’: The Construction of Postcolonial Indonesian Political Images, 1950s-1960s - Bambang Purwanto (Universitas Gadjah Mada, 2013)
This contribution is about how political images created in Indonesia in the immediate aftermath of decolonization acquired a divisive rather than a unifying character. The answer is sought in the tendency towards guidance that came to the fore during the Guided Democracy and Guided Economy. The analysis starts with matters of periodization arguing that the Guided Democracy and Guided Ecoomy in fact began in early 1957. Then, the economic content of the newly created post-colonial images is surveyed. Finally, the article takes a closer look at the precise role played in this process by Soekarno and Hatta. The article concludes by pointing out the great diversity of perceptions of the Guided Economy and also the relatively weak economic substance in these perceptions.